Manifestaciones oculares en segmento anterior en pacientes diagnosticados con virus de inmunodeficiencia humana, y alteraciones en la superficie ocular en pacientes en terapia antirretroviral. (2023)
The human immunodeficiency virus is transmitted through blood, semen and vaginal fluids. The virus is responsible for destroying cells T-CD4 lymphocyte defense. When CD4 counts are very low, the body will be exposed to multiple opportunistic infections, which is called stage Acquired immunodeficiency syndrome (AIDS) (1)